Effect of microstructure on the abrasive wear properties of infiltrated tungsten alloys - Caceres P.G. (2002)
The author gratefully acknowledges Engr. Guil-lermo Weston of Boyles Brothers Diamantina for hismaterial and technical support and cooperation withthe experiments. The financial support of the ConsejoNacional de Ciencia y Tecnologia (CONCYTEC) andthe Direccion Academica de Investigacion of thePontificia Universidad Catolica del Peru is alsogratefully acknowledged.